2013
DOI: 10.1038/nrmicro3143
|View full text |Cite
|
Sign up to set email alerts
|

A decade after SARS: strategies for controlling emerging coronaviruses

Abstract: Two novel coronaviruses have emerged in humans in the 21st century, Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and Middle East Respiratory Syndrome human coronavirus (MERS-CoV), both of which cause acute respiratory distress syndrome (ARDS) and have high mortality rates. There are no clinically approved vaccines or antiviral drugs available for either of these infections; thus, a priority in the field is the development of effective therapeutic and preventive strategies that can be readily applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
618
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 642 publications
(637 citation statements)
references
References 151 publications
(197 reference statements)
2
618
0
17
Order By: Relevance
“…Although accessory proteins vary among coronaviruses and may also include some strain-specific structural glycoproteins, the order of the structural protein genes is highly conserved as S, E, M, and N. The ∼180-kDa spike glycoprotein mediates entry into the host cell and surrounds the virus particle, yielding a crown-like appearance. Coronaviruses utilize a variety of cellular proteins as receptors (4,5); cleavage of the spike protein is crucial for mediating virus-host membrane fusion and subsequent entry into the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Although accessory proteins vary among coronaviruses and may also include some strain-specific structural glycoproteins, the order of the structural protein genes is highly conserved as S, E, M, and N. The ∼180-kDa spike glycoprotein mediates entry into the host cell and surrounds the virus particle, yielding a crown-like appearance. Coronaviruses utilize a variety of cellular proteins as receptors (4,5); cleavage of the spike protein is crucial for mediating virus-host membrane fusion and subsequent entry into the cell.…”
Section: Introductionmentioning
confidence: 99%
“…This stage of the disease is generally followed by increased fibroproliferation and hyaline membrane formation; depending on the patient, these gross pathological changes may progress or resolve [13]. Unfortunately, risk factors to identify patients at high risk for ARDS development are still matter of research [14]. Sometimes, depending on the type of virus responsible for the pneumonia, viral infection can extend beyond the lung tissue; it was observed that an increase of plasmatic creatine kinase in patients with pH1N1 pneumonia is associated with higher mortality, suggesting myocarditis as potential explanation for the increase of creatine kinase [15].…”
mentioning
confidence: 99%
“…Enfin, on assiste depuis quelques décennies à des phénomènes d'émergence virale liés à l'anthropisation des espaces naturels, qui facilitent la transmission des virus animaux à l'homme. L'épidémie de MERS-CoV (Middle East respiratory syndrome coronavirus) est ainsi un exemple récent d'émergence virale [4].…”
Section: Revuesunclassified